THE STRUCTURE, SYNTHESIS, AND APPLICATIONS OF POLYPHOSPHAZENES POLYMERS: MINI-REVIEW - Putra, Riandy; Hertiningtyas, Carissa (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2024)
The advancement of technology in inorganic polymers and their application in diverse sectors like electronics, medicine, and defense has experienced significant growth. Studies indicate that artificially created inorganic polymers can display distinct physical and chemical characteristics. Among these, polyphosphazenes stand out as a widely explored category, with over seven hundred polymers successfully synthesized. These polymers possess exceptional attributes such as self-extinguishing behavior, hydrophobicity, and biocompatibility, making them a focal point for researchers in the field of polymer science. The distinctive features are attributed to the phosphazene main chain, which incorporates two side groups in each repetitive unit, allowing for the substitution with other organic compounds to manifest various specific properties.